44.6k views
3 votes
Evaluate ( a=2 b=3)...3a - 2b =​

User Ran
by
5.8k points

2 Answers

0 votes

Answer:

0

Step-by-step explanation:

If a equals 2 and b equals 3, plug in the 2 to the a and the 3 to the b.

3(2) - 2(3)

3 ⋅ 2 = 6

-2 ⋅ 3 = -6

6 - 6 = 0

I hope this helps!

User Marduk
by
5.8k points
4 votes

Hey!

---------------------------------------------------

Steps To Solve:

~Substitute

3(2) - 2(3)

~Subtract

6 - 6

~Simplify

0

---------------------------------------------------

Answer:


\Large\boxed{\mathsf{0}}

---------------------------------------------------

Hope This Helped! Good Luck!

User J Ng
by
5.3k points